Assessing Soil Erosion in Bireuen District Aceh using USLE and GIS Models - Muhammad Nur; Halus Satriawan; Ernawita Ernawita; Cut Ayu Lizar (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Intensive land use in various fields allows land degradation to occur. One form of land degradation is soil erosion. This research aims to get an overview of the distribution of soil erosion in Bireuen Regency on various land uses. This research uses a descriptive survey research method with the Universal Soil Loss Equation (USLE) method approach and Geographic Information Systems. This research was conducted from June to August 2024, and the research area covered 17 sub-districts in the Bireuen district. To generate erosion distribution, data such as 10-year rainfall, land use type and soil biophysics were used. These data were obtained from BMKG, the World Rainfall Data Centre (CHRIPS), the Geospatial Information Agency, and DEMNAS. The data was then analyzed using the USLE equation and Arc GIS.10.8 software. The results of data analysis obtained that the distribution of soil erosion rates in Bireuen Regency consists of 0-20 tonnes/ha/year covering 84,297 ha, 20-60 tonnes/ha/year covering 41,327.34 ha, 60-180 tonnes/ha/year covering 32,954.82 ha, 180-480 tonnes/ha/year covering 17050.34 ha, and > 480 tonnes/ha/year covering 3,502.48 ha. Based on the classification of erosion hazard classes, the Bireuen Regency area has erosion at a very light-heavy level. The government and other stakeholders must apply sufficient soil conservation technology to produce sustainable land use.